Factors associated with HER2 overexpression in breast cancer: Experience in an Asian developing country - Tan, G.; Choo, W.; Taib, N.A.; Yip, C. (West Asia Organization for Cancer Prevention, 2009)
HER2 overexpression was observed in 30.3% of Malaysian female breast cancer patients. This group of patients represents a more aggressive subtype of breast cancer with higher tumour grade, PR negativity and lymphovascular positivity. No significant relationship was established between HER2 overexpression and age, race, lymph node, ER, pathology subtype and stage of disease from this study.